Biocompatible polyvinyl alcohol nanofibers loaded with amoxicillin and salicylic acid to prevent wound infections. - ŞAHİN, ALİ (My University, 2023)
Diabetic wounds are one of the most challenging clinical conditions in diabetes, necessitating the development of new treatments to foster healing and prevent microbial contamination. In this study, polyvinyl alcohol (PVA) was used as a matrix polymer, and amoxicillin (AMX) and salicylic acid (SA) were selected as bioactive compounds with antimicrobial (with AMX) and anti-inflammatory action (with SA) to obtain innovative drug-loaded electrospun nanofiber patches for the management of diabetic wounds. Scanning electron microscopy (SEM) images revealed the uniform and beadless structure of the nanofiber patches. Mechanical tests indicated that AMX minimally increased the tensile strength, while SA significantly reduced it. The patches demonstrated effective antibacterial activity against both grampositive (Staphylococcus aureus) and gram-negative (Escherichia coli) strains. The potential of these patches in the development of novel wound dressings is highlighted by the excellent biocompatibility with fibroblast cells maintained for up to 7 days. Keywords: antibiotic; wound dressing; biocompatibility; antimicrobial activity, drug delivery
Keywords: antibiotic; wound dressing; biocompatibility; antimicrobial activity; drug delivery